AN INFLUENCE OF BENTONITE ADDITION ON PERMEABILITY COEFFICIENT OF FLY ASH - Przemysław Baran (Inżynieria Ekologiczna, 2017)
The aim of the tests was to determine changes in the permeability coefficient of fly ash by adding 2, 5 and 10% of bentonite. Since a fly ash, due to its internal structure, can be a sealing material, contemporaneously, its acquisition does not involve high costs, the Authors considered the possibility of combining it with a small addition of bentonite to produce a relatively inexpensive sealing material. During the tests the permeability coefficient was indicated using an eodemeter with a variable hydraulic gradient on laboratory prepared tests samples at compaction index 0,95. As a result of carried out tests it was noted that even small (2%) bentonite addition caused reduction of a permeability coefficient by one order of magnitude relative to starting value. At the addition of 10% it was noted a reduction by two orders of magnitude of the mentioned parameter. Looking from “characteristic flow water” and “classification of permeability”, it can conclude that the pure ash has weak flow water characteristic and low classification of permeability; the 2% addition of bentonite makes the mixtures has a very low classification of permeability, while the addition of 10% gets these material impermeable from practical point of view.